Comparison between mitochondrial and chloroplast DNA variation in the native range of Silene vulgaris - Storchová, Helena; Olson, Matthew S (Molecular ecology, 2004)
A detailed survey of mitochondrial and chloroplast diversity in eight populations of Silene vulgaris from Central Europe was conducted for comparison with previously published data on diversity from S. vulgaris populations in the introduced range. Mitochondrial DNA (mtDNA) variation around the coxI gene was assessed with Southern blotting/restriction fragment length polymorphism methods. Chloroplast variation was assessed by sequencing the intergenic spacer separating the trnH and psbA genes. Thirty mtDNA haplotypes and 24 chloroplast DNA (cpDNA) haplotypes were found within 86 individuals. The overall genetic diversity h (0.941 for mitochondrial, and 0.893 for chloroplast markers) and within-population diversity were higher than reported in previous population studies of S. vulgaris in the USA and Europe. The frequency of private alleles was surprisingly high - more than 90% for both kinds of markers. Most of our populations were large and located in relatively undisturbed meadows, whereas surveys in Virginia consisted of smaller roadside populations. The slow rate of population turnover in European populations is discussed as a factor responsible for the relatively high diversity of S. vulgaris in undisturbed areas of its native range. Association between mtDNA and cpDNA haplotypes was also demonstrated. Finally, gender and mtDNA haplotype were associated in the Alps populations, where females were very rare.
Keywords: DNA chloroplastová; mitochondriální DNA; DNA, Mitochondrial; sekvence nukleotidů; haplotypy; zeměpis; Silene; genetická variace; Crosses, Genetic; Southernův blotting; Reproduction; Sequence Analysis, DNA; sekvenční analýza DNA; Europe; molekulární sekvence - údaje; Haplotypes; Geography; rozmnožování; Evropa; křížení genetické; DNA, Chloroplast; polymorfismus délky restrikčních fragmentů; Molecular Sequence Data; Base Sequence; Genetic Variation; Blotting, Southern; Polymorphism, Restriction Fragment Length